Racism, African American Women, and Their Sexual and Reproductive Health: A Review of Historical and Contemporary Evidence and Implications for Health Equity - Cynthia Prather; Taleria R. Fuller; William L. Jeffries; Khiya J. Marshall; A. Vyann Howell; Angela Belyue-Umole; Winifred King (Mary Ann Liebert, 2018)
Background: The sexual and reproductive health of African American women has been compromised due to multiple experiences of racism, including discriminatory healthcare practices from slavery through the post-Civil Rights era. However, studies rarely consider how the historical underpinnings of racism negatively influence the present-day health outcomes of African American women. Although some improvements to ensure equitable healthcare have been made, these historical influences provide an unexplored context for illuminating present-day epidemiology of sexual and reproductive health disparities among African American women. Methods: To account for the unique healthcare experiences influenced by racism, including healthcare provision, we searched online databases for peer-reviewed sources and books published in English only. We explored the link between historical and current experiences of racism and sexual and reproductive health outcomes. Results: The legacy of medical experimentation and inadequate healthcare coupled with social determinants has exacerbated African American women's complex relationship with healthcare systems. The social determinants of health associated with institutionalized and interpersonal racism, including poverty, unemployment, and residential segregation, may make African American women more vulnerable to disparate sexual and reproductive health outcomes. Conclusions: The development of innovative models and strategies to improve the health of African American women may be informed by an understanding of the historical and enduring legacy of racism in the United States. Addressing sexual and reproductive health through a historical lens and ensuring the implementation of culturally appropriate programs, research, and treatment efforts will likely move public health toward achieving health equity. Furthermore, it is necessary to develop interventions that address the intersection of the social determinants of health that contribute to sexual and reproductive health inequities.